African-American Accountants Then and Now: A Longitudinal Study of Factors Influencing Perceptions of the Workplace - Tammi C. Redd; Glen D. Moyes; Jun Sun (Journal of Accounting, Business and Management (JABM), 2011)
This study addresses the question of whether African-American accounting professionals perceive levels of job satisfaction and other work attributes differently over time as they gain experience in accounting practice. We examine how the elements that influence job satisfaction and perceptions of the workplace have changed over time for these accounting professionals. We contend that the evolution of the workforce and work itself have set forth contemporary workplace attitudes challenging Herzbergs (1959, 1966) Two-Factor Theory. Archival and newly collected data are combined to generate a longitudinal perspective on the African-Americans perception of job satisfaction and other work attributes specific to the field of accounting. The results reveal significant increases in the level of workload job stress and the overall level of job satisfaction, countered with significant decrease in professional-family conflict and discrimination applied to promotion.